Whole‐Heart Coronary MRA with 3D Affine Motion Correction Using 3D Image‐Based Navigation. Issue 1 (11th February 2013) - Henningsson, Markus; Prieto, Claudia; Chiribiri, Amedeo; Vaillant, Ghislain; Razavi, Reza; Botnar, René M
<x xml:space="preserve">Abstract</x> Purpose Robust motion correction is necessary to minimize respiratory motion artefacts in coronary MR angiography (CMRA). The state‐of‐the‐art method uses a 1D feet‐head translational motion correction approach, and data acquisition is limited to a small window in the respiratory cycle, which prolongs the scan by a factor of 2–3. The purpose of this work was to implement 3D affine motion correction for Cartesian whole‐heart CMRA using a 3D navigator (3D‐NAV) to allow for data acquisition throughout the whole respiratory cycle. Methods 3D affine transformations for different respiratory states (bins) were estimated by using 3D‐NAV image acquisitions which were acquired during the startup profiles of a steady‐state free precession sequence. The calculated 3D affine transformations were applied to the corresponding high‐resolution Cartesian image acquisition which had been similarly binned, to correct for respiratory motion between bins. Results Quantitative and qualitative comparisons showed no statistical difference between images acquired with the proposed method and the reference method using a diaphragmatic navigator with a narrow gating window. Conclusion We demonstrate that 3D‐NAV and 3D affine correction can be used to acquire Cartesian whole‐heart 3D coronary artery images with 100% scan efficiency with similar image quality as with the state‐of‐the‐art gated and corrected method with approximately 50% scan efficiency. Magn Reson Med 71:173–181, 2014. © 2013 Wiley Periodicals, Inc.